LDL-C targets based on coronary artery calcium: advancing Figure 6 from the 2022 American college of cardiology expert consensus decision pathway - Semenawit Burka; Ehimen Aneni; Thorsten Leucker; Michael J. Blaha (American Journal of Preventive Cardiology, 2025)
The approach to LDL-C management in primary prevention has shifted from lipid-centric strategies to personalized, risk-based frameworks. However, the binary distinction between primary and secondary prevention may overlook individuals with advanced subclinical atherosclerosis. Coronary artery calcium (CAC) scoring has become central in identifying such patients, especially those whose risk exceeds that implied by traditional risk calculators.The 2022 ACC Expert Consensus Decision Pathway (ECDP) incorporated CAC into LDL-C goal-setting, advocating for LDL-C < 70 mg/dL when CAC >100 or >75th percentile. Emerging evidence suggests that CAC ≥300 portends risk comparable to clinical ASCVD, warranting even lower targets (<55 mg/dL). This editorial highlights how Figure 6 from the 2022 ECDP offers a framework for reclassifying high-risk individuals and recommends that future guidelines recognize CAC >300 as equivalent to secondary prevention.